Training and Mentoring on Supply Chain Finance for Smoked Fish SMEs in Rowosari District, Kendal Regency - Kartikasari, Lisa; Qomaruddin, Muhammad; Indriastuti, Maya (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The aim of this community service is to help Smoked Fish SMEs in Bulak and Ketapang Villages access additional working capital and build partnerships with suppliers, distributors, and consumers. The focus is on improving their understanding of capital loan procedures and enhancing their supply chain relationships to ensure business sustainability. Method: The approach includes assessing SMEs' knowledge of loan procedures, conducting training to improve their loan application and partnership-building skills, and monitoring the results to measure impact and effectiveness. Practical Applications: This initiative will enable SMEs to secure financing and strengthen partnerships, leading to improved business performance, market expansion, and overall sustainability, benefiting both the businesses and the local community. Conclusion: By increasing SMEs' knowledge of capital loans and partnerships, this activity enhances their ability to grow and sustain their businesses, contributing to local economic development and community welfare.